2010
DOI: 10.3109/14767058.2010.534830
|View full text |Cite
|
Sign up to set email alerts
|

The potential of 4D sonography in the assessment of fetal behavior in high-risk pregnancies

Abstract: KANET test has the potential to detect and discriminate normal from borderline and abnormal fetal behavior in normal and in high-risk pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 310 publications
(57 citation statements)
references
References 30 publications
0
57
0
Order By: Relevance
“…Fetal KANET scores from low-risk and high-risk pregnancies were compared, and the difference was statistically significant. 59 Statistically significant difference was found between KANET scores of the fetuses from the low-risk group compared to the following subgroups of the high-risk group: previous child diagnosed with CP, hypertension (RR > 160/100), threatened preterm delivery, maternal fever, IUGR, Rh isoimmunization, placental bleeding. Furthermore, KANET scores significantly differed comparing threatened preterm delivery with PPROM vs threatened preterm delivery without PPROM; hypertension above 160/100 mm Hg vs hypertension below 160/100 mm Hg; diabetes before pregnancy vs gestational diabetes; IUGR with decreased resistance index (RI) of middle cerebral artery (MCA) vs IUGR without decreased RI of MCA; and Rh isoimmunization without hydrops fetalis vs Rh isoimmunization with hydrops fetalis.…”
Section: Prenatal Neurological Assessmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Fetal KANET scores from low-risk and high-risk pregnancies were compared, and the difference was statistically significant. 59 Statistically significant difference was found between KANET scores of the fetuses from the low-risk group compared to the following subgroups of the high-risk group: previous child diagnosed with CP, hypertension (RR > 160/100), threatened preterm delivery, maternal fever, IUGR, Rh isoimmunization, placental bleeding. Furthermore, KANET scores significantly differed comparing threatened preterm delivery with PPROM vs threatened preterm delivery without PPROM; hypertension above 160/100 mm Hg vs hypertension below 160/100 mm Hg; diabetes before pregnancy vs gestational diabetes; IUGR with decreased resistance index (RI) of middle cerebral artery (MCA) vs IUGR without decreased RI of MCA; and Rh isoimmunization without hydrops fetalis vs Rh isoimmunization with hydrops fetalis.…”
Section: Prenatal Neurological Assessmentmentioning
confidence: 97%
“…58 New results regarding the potential of 4D sonography in the assessment of fetal behavior in high-risk pregnancies were recently published. 59 The group in Khartoum applied KANET to large number of fetuses during the period of one year. The aim of the study was to assess the behavior in large sample of fetuses from normal and high-risk pregnancies by application of the KANET scoring test and to compare the scores obtained in low-and high-risk pregnancies.…”
Section: Prenatal Neurological Assessmentmentioning
confidence: 99%
“…A recent prospective longitudinal cohort study evaluating four-dimensional sonography in the assessment of fetal behavior in high-risk pregnancies [39] applied KANET in 620 singleton pregnancies between 26 and 38 weeks of gestation, in a 1-year period from January to December 2007. The study showed that KANET was able to identify borderline and abnormal fetal behavior in high-risk patient groups, such as gestosis and FGR [39] . These results support growing evidence that many neurological disorders originate from intrauterine rather than peri-or postnatal periods.…”
Section: Fetal Behaviormentioning
confidence: 99%
“…Previous studies clearly showed signifi cant differences in fetal behavior, in at risk-vs. normal pregnancies [1,39] . Several pathological processes are involved in triggering the process which leads to brain injury and results in alterations of fetal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Ten out of 36 fetuses with abnormal KaNeT had postnatal neurological evaluation after 2 and 6 months indicating seriously abnormal findings: four of them had severe generalized spasticity. 45 Honemeyer et al performed KaNeT test in 100 fetuses, with postnatal follow-up immediately after birth and at 12 weeks of age, with systematic neurological evaluation by a neonatologist. The results of pre-and postnatal scoring systems were compared, showing that normal prenatal KaNeT score is significantly predictive of the normal postnatal neurological examination of the newborn.…”
mentioning
confidence: 99%